Social economics and the solidarity city. - Murtagh, Brendan (Routledge, 2019)
The book explores the impact and potential of the social economy as a site of urban struggle, political mobilization and community organization. The search for alternatives to the neoliberal logic governing contemporary cities has often focused on broad and ill-defined political, social and environmental movements. These alternatives sometimesfail to connect with the lived realities of the city or to change the lives of those exploited in neoliberal restructuring. The book seeks to understand the capacity of the social economy to revitalize urban ethics, local practices and tangible political alterity. Providing a critical account of the social economy and its place in urban and state restructuring, the book draws on a range of international cases to argue that the social economy can be made a transformative space. Evaluating community enterprises, social finance, and solidarity economics, author Brendan Murtagh maps the possibilities, contradictions and tactics of moving the rhetoric of the just city into local and global action.
Keywords: Stadtökonomie; Stadtsoziologie; Kommunalpolitik; Gemeindeunternehmen; Armut; Sozialpolitik; Gemeinwirtschaft; Stadtentwicklung; Sozialökonomie; Solidarität; Stadtbevölkerung; Lebensbedingungen; Lebensqualität; Sozialwirtschaft; Soziales Unternehmen; Non-Profit-Organisation